Propuesta de mejora al proceso de escritura, presentación y aprobación de proyectos de Vinculación con la Comunidad de la ESPAM MFL - Robalino Zambrano, Martha Sofía (2017)
The present investigation was born from the need to know: How to improve the processes of writing, presentation and approval of projects linking with the community of the ESPAM MFL? To do this, it was necessary to approach the objectives, both general and specific referred to in the first chapter of this research paper. To get the relevant information with respect to the variables investigative raised in this thesis, it was necessary to obtain bibliographic information from sources of valid and reliable, the same ones that are set out in the second chapter of this work. In addition, the techniques used were the interview and observation, on the other hand the methods used were the inductive and the deductive, and the type of investigation was the bibliographic and descriptive. With all of these research inputs, the results, which show that the process of writing, presentation and approval of projects linking with the community of the ESPAM MFL consists of 25 activities binding the same ranging from the implementation of the projects of linking up to signing the Convention, 19 of those activities, generate added value, and all these activities are necessary; on the other hand, the time devoted to the activities that generate value is 91 days, while that of the activities that are necessary are 116 days; through the application of the VAT (Value Added Tax) Index resulted in 78.45%; that is, it is an effective process, however, require improvements and optimization of the same.